A review of using thermoelasticity for structural integrity assessment - L. Marsavina; R.A. Tomlinson (Fracture and Structural Integrity)
The advances in the use of thermoelastic stress analysis (TSA) for fracture mechanics assessment are reviewed. The development of techniques to determine stress intensity factor is presented followed by the application of these techniques to fatigue crack growth, crack closure and the study of mixed mode cracks.